Countermeasure for Mould Growths in Operation Theatre - Teoh, Yan Heng; Teoh, Kai Dong; Heng, Zhi Kai; Koh, Ji Wei (2015)
This project tackles the problem of mould growth in operation theatre as there is a rise in post-operational fungal infection cases among most of the hospitals. This is due to the condensation happened on the walls which caused from the difference in temperature between rooms in hospital and outer surrounding. Hence, a research on how to counter against this issue is conducted to look for the best insulation method for rooms in hospital especially operation theatre. The right material was chosen through decision matrix method by judging whether its properties fulfil the most desired insulation. After that, the material with the thermal resistance which leads to looking for the thickness needed for the insulation of wall is found. Finally, a simulation was run to test whether the thickness works to insulate or not.